The Probability of Implementing Restorative Justice in Business Dispute Resolution - Anwar, Mashuril; Lilyana, Besti; Zatika, Dinda Anna (Yayasan Kawanad, 2025)
The research analyzes the urgency and success probability of restorative justice implementation in business dispute resolution. The study employs normative legal research methodology through statutory and conceptual approaches. Legal material collection utilizes literature studies by identifying, gathering, and inventorying relevant primary and secondary legal sources. The analysis results demonstrate that restorative justice application becomes essential in business dispute resolution as it provides efficient, economical solutions while preserving business relationships. The mechanism serves as a strategic alternative to rigid and costly litigation, strengthening legal certainty and business climate competitiveness in Indonesia. The success rate of restorative justice in business dispute resolution shows promising potential when supported by parties' willingness, competent facilitators, and clear regulatory frameworks.